Effective use of Penicillin to Improve Culture Yield for Mycobacterium tuberculosis - Pradhan, Sneha; Ghimire, Gokarna Raj; Shrestha, Shova (Tribhuvan University Journal of Microbiology, 2019)
Objective: To compare LJ media and LJ media with penicillin for the growth of Mycobacterium tuberculosis and contamination, in pulmonary tuberculosis (PTB) suspected patients. Methods: A total of 300 PTB suspected cases at National Tuberculosis center (NTC) for analyzed for culture and contamination. Early morning sputum samples were collected in sterile leak-proof falcon tube. Digestion, decontamination and homogenization of sputum were done using NALC-NaOH (Modified Petroff method). The sputum sample was processed on LJ media and penicillin added LJ media and incubated at 37. Cultures were examined after 8 weeks. Results: All the PTB suspected cases were compared in LJ media and LJ media with penicillin, 29.7% (89) were positive, 21% (63) were contaminated on LJ media whereas 41% (123) were positive, 3.7 % (11) were contaminated on penicillin added LJ media. Also, 25 (8%) were 1+ grading, 14 (4.7%) were 2+ grading, whereas 81 (27%) and 45 (15%) were 3+ grading LJ + Penicillin and LJ media respectively. Conclusion: Contamination was reduced by 17.3% with the addition of penicillin to LJ media. And isolation of total positive cultures was enhanced by 11.3%.